2022
DOI: 10.3390/ijerph192114116
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Analysis on the Feasibility and Short-Term Efficacy of a Phase-III RCT on Mindfulness Added to Treatment as Usual for Patients with Chronic Migraine and Medication Overuse Headache

Abstract: This preliminary analysis of a single-blind phase-III RCT aims to compare the feasibility and short-term efficacy of mindfulness as an add-on to treatment as usual (TaU) in the management of patients with chronic migraine (CM) and medication overuse headache (MOH). Patients were randomized to either TaU (structured withdrawal of overused drugs, patient education and pharmacological prophylaxis) or TaU + MIND, wherein patients additionally received six 90 min weekly group sessions of mindfulness-based therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…Techniques such as relaxation training, mindfulness training, biofeedback, cognitive behavioral therapy, acceptance and commitment therapy, and motivational interviewing may show efficacy alone but can also support medical management. 42,43 Access to providers with expertise in these therapies can be limited and treatment can take time to implement. Also, depending on the health care system involved, there may be financial barriers to accessing these treatments.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques such as relaxation training, mindfulness training, biofeedback, cognitive behavioral therapy, acceptance and commitment therapy, and motivational interviewing may show efficacy alone but can also support medical management. 42,43 Access to providers with expertise in these therapies can be limited and treatment can take time to implement. Also, depending on the health care system involved, there may be financial barriers to accessing these treatments.…”
Section: Key Pointsmentioning
confidence: 99%
“…Biobehavioral management is important as well, especially in patients with comorbid psychiatric conditions like anxiety, depression, and obsessive-compulsive disorder. Techniques such as relaxation training, mindfulness training, biofeedback, cognitive behavioral therapy, acceptance and commitment therapy, and motivational interviewing may show efficacy alone but can also support medical management 42,43 . Access to providers with expertise in these therapies can be limited and treatment can take time to implement.…”
Section: Managementmentioning
confidence: 99%
“…По данным систематических обзоров и метаанализов, посвященных эффективности этих двух направлений майндфулнесс при мигрени, были сделаны следующие выводы [41,42]: а) майндфулнесс -это перспективный психологический метод, который можно комбинировать со стандартным лечением и получать бо ' льшую пользу, чем от монотерапии стандартным лечением или от монотерапии майндфулнесс; б) майндфулнесс значимо улучшает эмоциональное состояние пациентов, снижает уровень страдания, связанного с заболеванием, и улучшает качество жизни. У пациентов с мигренью и ЛИГБ в период отмены абузусных препаратов проведение терапии майндфулнесс имеет эффективность, сходную с традиционным профилактическим лечением [43,44].…”
Section: Characteristics Of Lifestyle Changes To Overcome the Negativ...unclassified
“…Behavioral therapies, namely relaxation, biofeedback, cognitive behavioral therapy (CBT), and mindfulness-based cognitive therapy, are helpful methods for minimizing the role of risk factors in CM patients. A phase 3 RCT comparing the feasibility and short-term efficacy of mindfulness added to treatment as usual and usual treatment alone for CM patients indicated that adding mindfulness to treatment as usual was feasible with short-term efficacy versus treatment without mindfulness [ 150 ]. A clinical study aimed at examining neuropsychological and neuropsychiatric characteristics of CM patients during the interictal phase concluded that CM patients showed a higher rate compared to healthy controls in cognitive domains (such as sustained attention, information processing speed, visuospatial episodic memory, working memory, and verbal fluency) and depressive and anxiety symptoms [ 151 ].…”
Section: Psychological Therapeutic Options In CMmentioning
confidence: 99%